Cholesteryl ester storage disease: a rare and possibly treatable cause of premature vascular disease and cirrhosis. Issue 11 (2nd September 2013) - Reynolds, Tim
Abstract : Cholesteryl ester storage disease (CESD) is an autosomal recessive lysosomal storage disorder caused by a variety of mutations of the LIPA gene. These cause reduced activity of lysosomal acid lipase, which results in accumulation of cholesteryl esters in lysosomes. If enzyme activity is very low/absent, presentation is in infancy with failure to thrive, malabsorption, hepatosplenomegaly and rapid early death (Wolman disease). With higher but still low enzyme activity, presentation is later in life with hepatic fibrosis, dyslipidaemia and early atherosclerosis.Identification of this rare disorder is difficult as it is essential to assay leucocyte acid phosphatase activity. An assay using specific inhibitors has now been developed that facilitates measurement in dried blood spots. Treatment of CESD has until now been limited to management of the dyslipidaemia, but this does not influence the liver effects. A new enzyme replacement therapy (Sebelipase) has now been developed that could change treatment options for the future.